Association of Physical Inactivity, Weight, Smoking, and Prior Injury on Physical Performance in a Military Setting - Teyhen, Deydre S. (J Athl Train, 2016)
CONTEXT: Although inactivity, being overweight, smoking, and a history of injury are identified as risk factors for poor health and injury, few authors have examined their association on physical performance. Young adults may be more likely to adopt healthier lifestyles if they understand the effect of health behaviors on performance. OBJECTIVE: To determine the association of being overweight, smoking, inactivity, and a history of injury with physical performance. DESIGN: Cross-sectional study. SETTING: Military population. PATIENTS OR OTHER PARTICIPANTS: Active-duty service members (N = 1466; 1380 men, 86 women; age = 24.7 ± 5.0 years; body mass index = 26.7 ± 3.4 kg/m(2)). MAIN OUTCOME MEASURE(S): Participants performed 8 measures (the triple-crossover hop for distance, the 6-m timed-hop test, the Functional Movement Screen, the Lower Quarter Y-Balance Test, the Upper Quarter Y-Balance Test, and the 3-event Army Physical Fitness Test) for evaluation of endurance, strength, muscular endurance, power, agility, balance, and motor control. Participants were categorized based on the number of health risk factors present. Using an analysis of covariance, we assessed the relationship between risk factors and physical performance with age and sex as covariates. RESULTS: Compared with those who had no risk factors (27.9% of men, 34.9% of women), physical performance was worse in those who had 1, 2, or 3 to 4 risk factors present by 4.3%, 6.7%, and 10.3%, respectively. Decrements in performance for those with 3 to 4 risk factors ranged from 3.3% to 14.4%. CONCLUSIONS: An unhealthy lifestyle habit or a history of injury was negatively associated with physical performance. Physical performance decrements were associated with the number of risk factors present. Understanding how risk factors contribute to decreased physical performance may enable clinicians to improve compliance with injury-prevention programs in occupational settings in which a young and relatively healthy workforce may be more concerned about performance than health.